Pervaporative Desalination by HKUST-1 and GrO@HKUST-1 Doped Sodium Alginate Hybrid Membrane - Ünlü, Derya (Konya Teknik Üniversitesi, 2022)
In this study, HKUST-1 and GrO@HKUST-1 metal organic framework were synthesized and added to the sodium alginate membrane for the manufacture of hybrid membranes to use in pervaporative desalination. The hybrid membranes were characterized by using FTIR, XRD, SEM, TGA and contact angle. The effects of HKUST-1 and GrO@HKUST-1 content in the sodium alginate membrane, feed NaCl concentration, and operation temperature were assessed for the flux and salt rejection. The addition of HKUST-1 and GrO@HKUST-1 to the sodium alginate membrane improved the purification performance in pervaporative desalination applications. The optimal loading ratios for HKUST-1 and GrO@HKUST-1 were specified as 3 wt% HKUST-1 and 3 wt% HKUST-1@GO, respectively. Optimum operation parameters were achieved at 60oC of temperature and a 4 wt% of feed NaCl concentration for both hybrid membranes. Hybrid membranes (GrO@HKUST-1 doping) exhibited excellent desalination performance with salt rejections of 99,99% and water fluxes of 6,59 kg/m2h.

Bu çalışmada HKUST-1 ve HKUST-1@GOmetal organik kafes yapıları sentezlenmiş ve sodyum aljinat membrana eklenerek pervaporatif desalinasyon için hibrit membranlar üretilmiştir. Hibrit membranlar FTIR, XRD, SEM, TGA ve temas açısı kullanılarak karakterize edilmiştir. Sodyum aljinat membrana ilave edilen HKUST-1 ve HKUST-1@GO miktarının, besleme tuz konsantrasyonunun ve operasyon sıcaklığının akı ve tuz giderimine etkisi incelenmiştir. Pervaporatif desalinasyon uygulamalarında sodyum aljinat membrana HKUST-1 ve HKUST-1@GO ilavesi membranın saflaştırma performansını iyileştirmiştir. Optimum HKUST-1 ve HKUST-1@GO yükleme oranı ağırlıkça %3 olarak belirlenmiştir. Optimum operasyon parametreleri 60oC sıcaklık ve ağırlıkça %4 besleme tuz konsantrasyonu olarak her iki hibrit membran için belirlenmiştir. Hibrit membranlar mükemmel desalinasyon performansı sergilemiş ve en yüksek ayırma performansı HKUST-1@GO yüklü hibrit membran ile %99,99 tuz giderimi ve 6,59 kg/m2h su akısı olarak elde edilmiştir.
HKUST-1 ve GrO@HKUST-1 KATKILI SODYUM ALJİNAT HİBRİT MEMBRANLARIN PERVAPORATİF DESALİNASYONU
211N006
Keywords: Engineering; Mühendislik